2007
DOI: 10.1002/app.26228
|View full text |Cite
|
Sign up to set email alerts
|

Transparent photo‐curable co‐polyacrylate/silica nanocomposites prepared by sol‐gel process

Abstract: This work prepared the highly transparent photo-curable co-polyacrylate/silica nanocomposites by using sol-gel process. The FTIR and 13 C NMR analyses indicated that during the sol-gel process, the hybrid precursors transform into composites containing nanometer-scale silica particles and crosslinked esters/anhydrides. Transmission electron microscopy (TEM) revealed that the silica particles within the average size of 11.5 nm uniformly distributed in the nanocomposite specimen containing about 10 wt % of Si. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Thus, photo-curable polyacrylate nanocomposite with silica gel nanoparticles is prepared by sol-gel synthesis. In contrast to the ordinary sol-gel process (using water for liquid), in this work hydrolysis of the precursor was conducted through air moisture in order to confine size of silica gel nanoparticles to nanometer scale and protect the composite from residual water molecules [277]. Morphology of crystals in polyurethane cast films (PU) with different gold particles content 0.1, 0.3 and 1.0 % is studied (Fig.…”
Section: Morphology and Fractal Models Of Hybrid Nanocompositesmentioning
confidence: 99%
“…Thus, photo-curable polyacrylate nanocomposite with silica gel nanoparticles is prepared by sol-gel synthesis. In contrast to the ordinary sol-gel process (using water for liquid), in this work hydrolysis of the precursor was conducted through air moisture in order to confine size of silica gel nanoparticles to nanometer scale and protect the composite from residual water molecules [277]. Morphology of crystals in polyurethane cast films (PU) with different gold particles content 0.1, 0.3 and 1.0 % is studied (Fig.…”
Section: Morphology and Fractal Models Of Hybrid Nanocompositesmentioning
confidence: 99%
“…[9][10][11] Inappropriate UV curing deteriorates the mechanical properties [12] and electrical properties [13,14] of polymeric resins. In the previous studies, we reported the preparation and property characterizations of transparent, UV-curable co-polyacrylate/ silica nanocomposite resins [15] and it has been successfully applied to the direct encapsulation of a bottom-emitting OLED. [16] In this work, a systematic study on the effects of UV curing and post-baking treatments on the electrical properties of such a nanocomposite sealing resins is presented.…”
Section: Full Papermentioning
confidence: 99%
“…[15] The ingredients of nanocomposite resins were the oligomer (bisphenol A epoxy diacrylate, see Figure 1 for its chemical structure) purchased from Sartomer Co., the radical photopolymerization initiator (1-hydroxycyclohexylphenyl ketone) obtained from Chembridge International Co., acrylic acid and tetraethyl orthosilica (TEOS) purchased from Aldrich Chemicals Co. Preparation of nanocomposite resin is briefly described as follows.…”
Section: Experimental Part Preparation Of the Nanocomposite Resinmentioning
confidence: 99%
See 2 more Smart Citations